Modified talc powder masterbatch and film
Patent Information
- Application Number
- CN202611004769.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-16
AI Technical Summary
专利CN 120757922 提出了一种耐高温食品包装膜及其制备方法,其中无机组分滑石粉添加量占比较低,且制备流程较为繁琐
[0015]本发明将滑石粉作为无机填料填充,利用其独特的片层结构可在聚合物基体中形成“迷宫阻隔效应”,显著延长气体、水分子的渗透路径,大幅提升薄膜的阻隔性能,同时能有效增强材料的刚性、抗蠕变性与加工成型性。本发明利用酒石酸将滑石粉进行界面改性,酒石酸分子中的羧基和羟基能够与滑石粉片层边缘的Si—OH、Mg—OH及Mg2+通过酯化、强氢键或五元/六元螯合作用形成稳定的有机锚定包覆层,这层有机界面显著降低了滑石粉的表面能并赋予其亲油性,从而大幅改善与高分子熔体的润湿性和相容性,提升了其与烯烃组分的界面相容性,减少团聚,同时,该包覆层所带来的空间位阻效应及可能的静电排斥,有效削弱了粒子间的范德华力和氢键团聚驱动力,使滑石粉在熔融剪切作用下更容易被剥离和分散,最终实现母粒和薄膜中的高度均匀分散。采用熔融挤出的工艺制备母粒,实现了滑石粉在烯烃组分中的40%-80%的高填充,制备的母粒均匀,未出现开裂及黄变现象,有效降低了烯烃组分的使用,极大的降低了原料成本。
Smart Images

Figure CN122917422A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of modified plastics technology, and more particularly to a modified talc masterbatch and film. Background Technology
[0002] Food packaging films play a crucial role in the food supply chain and are the most widely used substrate in the flexible packaging sector. With the high-quality upgrading of my country's food industry, the food packaging film industry is developing towards safety and compliance, functional integration, high cost-effectiveness, and green and low-carbon practices. Currently, commercially available food packaging films are mainly made of polyolefin materials, whose raw materials are derived from non-renewable petroleum resources, resulting in high costs and significant susceptibility to fluctuations in oil prices. Furthermore, pure polyolefin substrates have inherent defects such as insufficient oxygen and water vapor barrier properties and poor mechanical properties, making it difficult to meet the packaging requirements of food.
[0003] Inorganic mineral powder filling modification can effectively improve the performance of polyolefin packaging films, reduce production costs, and decrease the amount of petroleum-based resin used. Talc, as a typical 2:1 type layered hydrous magnesium silicate mineral, possesses a regular two-dimensional lamellar structure, excellent thermal stability, natural hydrophobicity, and food contact compliance. Compared with other inorganic fillers such as calcium carbonate, kaolin, and montmorillonite, its unique lamellar structure can form a "maze barrier effect" in the polymer matrix, significantly extending the permeation path of gas and water molecules, greatly improving the barrier performance of the film, and effectively enhancing the rigidity, creep resistance, and processability of the material. It is a high-quality inorganic filler for modifying food packaging films and has extremely high application value and industrialization prospects in the food packaging field.
[0004] In China, the inorganic component filling content of existing film products is generally below 30%. When the filling content exceeds 30%, the poor interfacial compatibility between the inorganic component and the non-polar polyolefin matrix leads to powder agglomeration and increased brittleness of the masterbatch. This can significantly reduce the tensile strength and elongation at break of the film. Patent application CN 118703028 A proposes a high-filling calcium carbonate antibacterial packaging film, where the inorganic calcium carbonate filling content is maintained between 30% and 35%. However, the actual filling content of the final formed film is still low, resulting in limited cost reduction and failing to fundamentally solve the problem of synergistic control between high filling and high performance. The olefin content remains relatively high, leading to higher costs. Patent CN 120757922 proposes a high-temperature resistant food packaging film and its preparation method, but the talc powder addition content is relatively low, and the preparation process is quite cumbersome. Currently used silane coupling agents for interfacial modification are prone to self-condensation, forming oligomer agglomerates, and are expensive with strict process control. Summary of the Invention
[0005] The purpose of this invention is to address the aforementioned shortcomings of existing technologies by providing a modified talc masterbatch and film. By modifying the talc, agglomeration of the talc filler is effectively avoided, resulting in a tighter interfacial bond, reduced interfacial voids and defects, and stronger interfacial adhesion. The talc masterbatch does not exhibit agglomeration or yellowing issues even under high-filling conditions, effectively reducing the use of olefin components and significantly lowering the masterbatch cost.
[0006] The first objective of this invention is to provide a modified talc masterbatch, which is prepared by a twin-screw extruder from the following components in parts by weight: 40-80 parts modified talc, 20-60 parts carrier resin, 1-1.5 parts lubricant, 1-3 parts dispersant, and 0.4-0.6 parts oxidant; wherein the modified talc is talc loaded with tartaric acid.
[0007] Furthermore, the modified talc powder is prepared as follows: talc powder and tartaric acid are mixed and coated at high speed, and then heat-treated at 60-80 °C for 0.5-1.0 h.
[0008] Furthermore, the mass ratio of talc to tartaric acid is 100:1-2.
[0009] Furthermore, the modified talc powder is prepared as follows: tartaric acid and stearic acid are mixed, heated, and then atomized and sprayed onto the talc powder.
[0010] Furthermore, the carrier resin is one or more of polyethylene, polypropylene, polybutylene adipate / terephthalate, or polycaprolactone.
[0011] Furthermore, the carrier resin is a mixture of LLDPE and LDPE in a mass ratio of 6-7:3-4.
[0012] Further, the dispersant is one or more of PE wax, monoglyceride stearate, or glycerin; the lubricant is calcium stearate or magnesium stearate.
[0013] Furthermore, the oxidant is obtained by compounding pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] with tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1.
[0014] A second objective of this invention is to provide a modified talc film prepared using the aforementioned modified talc masterbatch.
[0015] This invention uses talc powder as an inorganic filler. Its unique layered structure creates a "labyrinth barrier effect" within the polymer matrix, significantly extending the permeation paths of gas and water molecules and greatly improving the barrier properties of the film. Simultaneously, it effectively enhances the material's rigidity, creep resistance, and processability. This invention utilizes tartaric acid to modify the interface of talc powder. The carboxyl and hydroxyl groups in tartaric acid molecules can react with the Si-OH, Mg-OH, and Mg groups at the edges of the talc powder layers. 2+ A stable organic anchoring coating layer is formed through esterification, strong hydrogen bonding, or five- or six-membered chelation. This organic interface significantly reduces the surface energy of talc and imparts oleophilicity, thereby greatly improving its wettability and compatibility with polymer melts, enhancing its interfacial compatibility with olefin components, and reducing agglomeration. Simultaneously, the steric hindrance effect and potential electrostatic repulsion brought about by this coating layer effectively weaken the van der Waals forces and hydrogen bond agglomeration driving forces between particles, making talc easier to peel off and disperse under melt shear, ultimately achieving highly uniform dispersion in masterbatches and films. Masterbatch preparation using melt extrusion technology achieves a high filling ratio of 40%-80% of talc in olefin components. The prepared masterbatches are uniform, without cracking or yellowing, effectively reducing the use of olefin components and significantly lowering raw material costs.
[0016] This invention utilizes a casting method to extrude highly filled talc masterbatch into films, achieving a talc content of 40%-80% in the final film product. This effectively improves the film's mechanical and barrier properties, eliminating the need for secondary masterbatch compounding; film can be formed from a single masterbatch application, with an adjustable thickness range. This invention has broad application prospects in the food packaging field. The raw materials used in this invention are readily available, and the preparation process is simple, highly operable, and easy for large-scale production.
[0017] This invention provides a high-filled talc masterbatch and film with high talc content, excellent comprehensive performance, simple preparation process, and adaptability to various molding processes. It has important practical significance for promoting the industrial application of talc deep processing, realizing the domestic substitution of food packaging materials and green and low-carbon development. Attached Figure Description
[0018] Figure 1 The Zeta potentials of the talc powder samples prepared in Examples 1, 2 and Comparative Examples 1-3; Figure 2 Infrared spectra of talc powder mineral samples prepared in Examples 1, 2 and Comparative Examples 1-3; Figure 3 The images show the appearance of the talc powder mineral samples prepared in Example 1 and Comparative Example 1. Detailed Implementation
[0019] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings to further illustrate the technical solutions of the present invention. However, the present invention is not limited to these embodiments.
[0020] The talc sample used was food-grade talc from Guiguang Talc K brand, with a particle size of 45 μm. The tartaric acid used was racemic tartaric acid (DL-).
[0021] Example 1: 100 parts of talc powder were mixed with 1% wt tartaric acid and stirred evenly. The mixture was then stirred at 1200 rpm for 30 min to coat the powder, followed by heat treatment at 60 °C for 0.5 h to ensure sufficient interaction between the tartaric acid and the talc powder interface, resulting in modified talc powder. Alternatively, tartaric acid can be sprayed through an 80 °C oil bath heated stearic acid atomizing nozzle. Aluminate esters and monoalkoxy titanates can also be selected as modifiers.
[0022] Example 2: 100 parts of talc powder were mixed with 2% wt tartaric acid and stirred evenly. The mixture was then coated at 1200 rpm for 30 min, followed by heat treatment at 60 ℃ for 0.5 h to obtain modified talc powder. Alternatively, tartaric acid can be sprayed through an 80 ℃ oil bath heated atomizing nozzle. Aluminate esters and monoalkoxy titanates can also be selected as modifiers.
[0023] Comparative Example 1: Talc powder without modification Comparative Example 2: 100 parts talc powder were mixed with 1 part stearic acid and stirred evenly. The mixture was then stirred at 1200 rpm for 30 min to coat the powder, followed by heat treatment at 60 ℃ for 0.5 h to obtain modified talc powder. Alternatively, stearic acid can be sprayed through a stearic acid atomizing nozzle heated by an 80 ℃ oil bath.
[0024] Comparative Example 3: 100 parts of talc powder were mixed with 0.5 parts of stearic acid and 0.5 parts of tartaric acid by uniform stirring for 1 hour, followed by heat treatment at 60 °C for 0.5 hours to obtain modified talc powder. Alternatively, tartaric acid and stearic acid can be sprayed through an 80 °C oil bath heated by a stearic acid atomizing nozzle.
[0025] Example 4: Preparation of Masterbatch The masterbatch composition is as follows: 56 parts of Dow Chemical (2048G) LLDPE and LyondellBasell (2426K) LDPE (7:3) were selected as the polymer masterbatch; 2.6 parts of Dinghai Plastics Chemical PE wax were selected as the powder dispersant; 1.0 part of Xingyi Chemical calcium stearate was selected as the lubricant and stabilizer; and 0.4 parts of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite were selected as the antioxidant in a 1:1 mixture.
[0026] Talc masterbatch was prepared by twin-screw extrusion granulation. First, all raw materials were weighed according to the formula to prepare a premix. LLDPE and LDPE carrier resin were added to a high-speed mixer and stirred at 300 rpm for 1 min. Then, PE wax, calcium stearate and antioxidant were added and stirred for another 2 min. Finally, the modified talc prepared in Example 1, Comparative Example 1 and Comparative Example 2 were added and mixed for 5 min. After obtaining a uniform premix, it was sealed for later use to prevent moisture absorption. Before extrusion, set the temperatures of zones 1 (feed inlet) to 6 of the twin-screw extruder to 140℃, 160℃, 175℃, 185℃, 190℃, and 190℃ respectively. After locking the brake casters, start heating and maintain a constant temperature for 30 minutes to ensure each zone reaches the target temperature. Then, start the main extruder and run it at 50 rpm unloaded for 2 minutes. Add a small amount of pure PE carrier resin to flush the barrel, screw, and die. After the material output is normal, proceed to the formal production stage. Gradually increase the main extruder screw speed to 250-300 rpm, simultaneously increase the feeding frequency and switch to premixed material. At the same time, start the vacuum pump to control the vacuum degree to ≥-0.09 MPa, and control the feeding rate to 2-4. kg / h, melt pressure 8-12MPa; after the die head extrudes a continuous and uniform strip, the strip is manually pulled through a cooling water tank at 30-35℃ for full cooling, and then the cooled strip is introduced into the traction machine and pelletizer. After the output stabilizes, the material is officially received; finally, the collected particles are screened to remove clumps and fine powder, and dried with hot air circulation at 60℃ for 2 hours until the moisture content is ≤0.1%. After passing the quality inspection, the particles are sealed and packaged.
[0027] Example 5: Preparation of talc packaging film Talc packaging film was prepared by single-screw extrusion, using the single masterbatch prepared in Example 4 throughout the process, without adding any additional PE resin. The temperatures of zones 1 (feed port) to 6 (die head) of the single-screw casting extruder were set to 140℃, 160℃, 175℃, 185℃, 190℃, and 190℃ respectively, with the casting cooling roller temperature at 25-30℃. After heating, the temperature was stabilized for 30 minutes. The extruder was first run unloaded at 50 rpm for 2 minutes, and the barrel and die head flow channel were rinsed with pure PE resin. After the discharge was normal, the dried masterbatch was added, and the extrusion was maintained at a stable speed of 30 rpm. The melt was rapidly cooled and shaped by the casting roller. The film thickness was controlled by adjusting the traction rate. Unstable samples were discarded during startup. After stabilization, the film was continuously wound up, and standard samples were cut for subsequent performance testing.
[0028] The tartaric acid-modified talc in Example 1 could reach a maximum addition of 80%, while the unmodified talc addition reached a maximum of 50%. This resulted in significant brittleness and breakage during masterbatch preparation, indicating poor compatibility between talc and masterbatch, making masterbatch preparation impossible. In this experiment, a 40% talc masterbatch was used for performance testing, focusing on its mechanical and barrier properties. The film thickness was 50-70 μm.
[0029] Particle size and zeta potential test analysis: Zeta potential and laser particle size distribution tests were conducted on aqueous dispersion systems of different talc powder samples (results are shown in Figure 1 and Table 1). The results showed that compared with unmodified talc powder (Comparative Example 1), talc powder modified with tartaric acid, stearic acid, and a combination of the two achieved significant particle size refinement, and the surface and interface charge characteristics showed differentiated control effects. Particle size tests showed that the D50 and D90 of unmodified talc powder were 16.83 μm and 41.43 μm, respectively. The D50 of all modified samples was reduced to below 12 μm, and the D90 was controlled to below 30 μm, confirming that surface modification can effectively break particle agglomeration and achieve ultrafine dispersion. Among them, the 1% tartaric acid modification (Example 1) showed the best particle size reduction effect, with D50 and D90 as low as 11.05 μm and 26.76 μm, respectively, which was better than the stearic acid modification with the same amount of addition (Comparative Example 2, D50 11.57 μm and D90 29.10 μm); the particle size control ability of the 2% tartaric acid modification (Example 2) and the tartaric acid-stearic acid compound modification (Comparative Example 3) was not significantly different from that of Example 1. Zeta potential testing showed that the surface of unmodified talc powder was negatively charged (approximately -18 mV). Different modification treatments had significant differences in the regulation of surface charge: 1% tartaric acid modification maintained the negative charge of the powder surface, and the potential value was close to that of the unmodified sample; 1% stearic acid modification further enhanced the negative charge (approximately -20 mV), which was the strongest among all samples. The higher absolute value of the potential means stronger electrostatic repulsion between particles, which is more conducive to the dispersion and stability of the system; tartaric acid-stearic acid compound modification weakened the surface negative charge (approximately -10 mV); while 2% tartaric acid modification achieved a reversal of surface charge polarity, and the potential changed from negative to positive (approximately +19 mV). This indicates that high addition of tartaric acid can change the interfacial charge properties of talc powder, possibly because at higher addition levels, magnesium ions dissolve, causing the charge to turn into a positive charge. In summary, 1% tartaric acid modification can simultaneously achieve efficient deagglomeration and refinement of talc powder and maintain surface charge stability, resulting in the best overall modification performance.
[0030] Table 1. Test results of different modified talc particle sizes
[0031] Infrared spectroscopy analysis: Infrared spectroscopy analysis was performed on the surface functional groups of different talc powder samples, and the test results are as follows: Figure 2 As shown, all samples retained 1000 cm³ of talc. - ¹ The characteristic absorption peaks of the Si-O and Mg-O-Si mineral frameworks below indicate that the modification did not destroy the bulk crystal structure of talc powder; the effect only occurred at the powder surface and interface. Compared with unmodified talc (Comparative Example 1), all modified samples showed characteristic absorptions of the organic modifier: 2800-3000 cm⁻¹ - A -CH2- and -CH3 alkyl stretching vibration peak appears at 3600 cm⁻¹. - ¹ The peak shape and intensity of the characteristic hydroxyl peaks in the vicinity changed significantly, confirming that the modifier was successfully loaded onto the talc surface and formed hydrogen bonds or chemisorption with the surface hydroxyl groups; 1000-1500 cm⁻¹ - ¹ The addition of a new carboxylate characteristic peak in the range further confirms that the modifier and talc form a stable interfacial chemical bond. Furthermore, the organic group characteristic peak intensity in Example 2 (modified with 2% tartaric acid) is higher than that in Example 1 (modified with 1% tartaric acid), indicating that increasing the amount of modifier can increase the loading of organic groups on the talc surface and enhance the modification effect.
[0032] Masterbatch appearance analysis: Figure 3 The comparison of the appearance of tartaric acid-modified talc masterbatch (Example 1) and unmodified talc masterbatch (Comparative Example 1) is shown. Both are white polymer filler masterbatches prepared by melt blending, extrusion, and pelletizing, but they show significant differences due to the different surface modification states of the talc: the masterbatch of Example 1 is large and uniform in size, with clear edges and flat end faces, standard short cylinders, clear boundaries between particles without adhesion or agglomeration, and a uniform milky white color with good gloss. This indicates that tartaric acid modification effectively improves the compatibility between talc and the polymer carrier, achieves uniform dispersion of the filler, stable melt flow, and smooth granulation process; while Comparative Example 1 shows that the masterbatch size is significantly smaller and the particle size distribution is extremely wide. It is mostly broken and fragmented, with severe particle agglomeration and adhesion. The overall appearance is uneven grayish-white with a dull luster and a large number of dark spots. The essence is that the surface polarity of the unmodified talc powder is strong and its compatibility with non-polar polymers is poor, which leads to its own agglomeration and causes fluctuations in melt flow. During extrusion and pelletizing, frequent breakage of strips produces a large amount of broken material. This difference in morphology directly determines the subsequent processing performance and product quality. Modified masterbatch has good processing stability and excellent product performance, while unmodified masterbatch is prone to problems such as filter clogging, rough product surface, and a significant decrease in mechanical properties.
[0033] Mechanical property analysis: Mechanical property testing was conducted in accordance with the standard specification "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets" (GB / T1040.3-2006), and an electronic universal testing machine was used to conduct tensile mechanical property testing on talc-based food packaging films. The experimental results are shown in Table 2. Tartaric acid-modified talc achieved the optimal balance between strength and toughness, and its comprehensive performance was significantly better than that of the unmodified and traditional stearic acid-modified systems. Its maximum force reached 27.59 N, which is 25.0% higher than that of pure PE film, and 13.0% and 44.1% higher than that of the unmodified and stearic acid-modified systems, respectively, greatly enhancing the tear and puncture resistance of the film in actual use. The tensile strength increased by 29.3% to 15.76 MPa compared with pure PE film. Although it is lower than that of the stearic acid-modified system (30.65 MPa), the toughness advantage is obvious. The tensile strain reached 190.8%, retaining 46.3% of the toughness of pure PE film, which is better than that of the stearic acid-modified system (166.8%) and much higher than that of the unmodified system (40.5%, which is only 9.8% of that of pure PE), thus solving the embrittlement problem under high filling conditions. The performance difference stems from the covalent bonds formed between tartaric acid and the talc surface, resulting in strong interfacial bonding and high stress transfer efficiency, making it an ideal solution for talc modification of food packaging films.
[0034] Table 2 Mechanical property tests of talc with different addition amounts
[0035] Barrier performance analysis: The water vapor transmission rate test of talc packaging film was conducted according to GB / T 1037-2021 "Test Method for Water Vapor Permeability of Plastic Films and Sheets - Cup Method". The specific test method is as follows: Add an appropriate amount of desiccant (anhydrous calcium chloride) to the permeation cup, ensuring the distance between the desiccant surface and the lower surface of the film is within 3-5 mm. Tightly cover the cup opening with the film sample (diameter larger than the cup opening) and seal it rigorously using sealing wax or a special sealing ring, ensuring that only the film area is a water vapor channel. Weigh the sealed permeation cup (accurate to 0.1 mg) and record it as W1. Place the permeation cup in a constant temperature and humidity chamber that has been stabilized under specific test conditions. After a certain interval, remove it and quickly weigh it in a dry environment (W2), then quickly return it to the chamber. Continue testing until a stable transmission state is reached (the difference in weight gain after three consecutive tests is approximately linear). The results are shown in Table 3.
[0036] Table 3 Water vapor transmission rate test
[0037] The results of the oxygen permeability tests on films prepared with different modified talc masterbatches are shown in Table 4. The overall experimental results indicate that tartaric acid-modified talc significantly improves the barrier properties of PE films compared to stearic acid-modified and unmodified talc: the water vapor permeability of the 1% tartaric acid-modified talc / PE composite film is only 2.76 g / (m²). (24h), the oxygen permeability was reduced by 98.6% compared to pure PE film and by 72.8% compared to the 1% stearic acid modified system; the oxygen permeability was 722.24 cm³ / (m²). 24h The oxygen permeability of the composite membrane was reduced by 81.1% compared to pure PE membrane and by 60.4% compared to the stearic acid modified system (0.1 MPa). However, the unmodified talc, due to agglomeration and the formation of numerous permeation defects, significantly increased the oxygen permeability of the composite membrane to 50,000 cm³ / (m²). 24h At pressures above 0.1 MPa, the barrier properties of the film are significantly inferior to those of pure PE film. This result confirms that tartaric acid-modified talc can improve the barrier properties of the film, providing a feasible path for the industrial production of low-cost, high-barrier food packaging films.
[0038] Table 4 Oxygen Transmission Performance Test
[0039] For any points not covered above, existing technologies shall apply.
[0040] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.
Claims
1. A modified talc masterbatch, characterized in that: The masterbatch is prepared by a twin-screw extruder from the following components in parts by weight: 40-80 parts modified talc, 20-60 parts carrier resin, 1-1.5 parts lubricant, 1-3 parts dispersant, and 0.4-0.6 parts oxidant. The modified talc is talc loaded with tartaric acid.
2. The modified talc masterbatch as described in claim 1, characterized in that: The modified talc powder is prepared as follows: talc powder and tartaric acid are mixed and coated at high speed, and then heat-treated at 60-80 ℃ for 0.5-1 h.
3. The modified talc masterbatch as described in claim 2, characterized in that: The mass ratio of talc to tartaric acid is 100:1-2.
4. The modified talc masterbatch as described in claim 1, characterized in that: The modified talc powder is prepared as follows: tartaric acid and stearic acid are mixed, heated, and then atomized and sprayed onto the talc powder.
5. The modified talc masterbatch as described in claim 1, characterized in that: The carrier resin is one or more of polyethylene, polypropylene, polybutylene adipate / terephthalate, or polycaprolactone.
6. The modified talc masterbatch as described in claim 5, characterized in that: The carrier resin is a mixture of LLDPE and LDPE in a mass ratio of 6-7:3-4.
7. The modified talc masterbatch as described in claim 1, characterized in that: The dispersant is one or more of PE wax, stearic acid monoglyceride, or glycerin; the lubricant is calcium stearate or magnesium stearate.
8. The modified talc masterbatch as described in claim 1, characterized in that: The oxidant is obtained by compounding pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] with tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:
1.
9. A modified talc film, characterized in that, It was prepared using the modified talc masterbatch described in any one of claims 1-8.